Good Corporate Governance Terhadap Kualitas Laporan Keuangan Dengan Sistem Informasi Akuntansi Sebagai Variabel Moderasi - Odorikus Otarman Gea; Robiur Rahmat Putra (Owner : Riset dan Jurnal Akuntansi, 2022)
Good corporate governance which is corporate governance has become a must to be implemented properly by companies, in addition to controlling, and ensuring the continuity of the company, good corporate governance can also provide added value to the company and affect the quality of investors' decisions in assessing a company. The purpose of this study was to examine the effect of good corporate governance on the quality of financial statements moderated by accounting information systems. This research method is a quantitative type of research, the population in this study is all employees who work in the financial accounting division involved in preparing financial statements in Jabodetabek. The sample in this study was determined by purposive sampling method . Data collection was carried out by distributing questionnaires and obtained 201 respondent data. The data analysis method used is Structural Equating Modeling-Partial Least Square (SEM-PLS) using smartPLS software version 3. The results of this study prove that good corporate governance directly affects the quality of financial statements, then the accounting information system also has a direct effect. on the quality of financial statements and accounting information systems are significantly able to moderate the influence of good corporate governance in influencing the quality of financial reports. The results of this study can be used as recommendations to companies to improve the quality of financial reports and provide evidence about the moderating impact of the application of Accounting Information Systems on the Effect of Good corporate governance on the Quality of Financial Reports